Sperm Selection Technology in ART - Martin, Catherine; Woodland, Emma (Seminars in Reproductive Medicine, 2021)
Intracytoplasmic sperm injection (ICSI) is a commonly used in vitro fertilization technique. Selection of sperm for injection is currently done using subjective assessment of morphology, which may not accurately identify the best-quality sperm. Hyaluronic acid receptors on sperm plasma membranes are a marker of maturity, and sperms which are capable of binding immobilized hyaluronic acid in vitro are of higher quality. This can be used as an advanced sperm selection technique to choose sperm for ICSI, termed physiological ICSI (PICSI). Several studies reported improved fertility treatment outcomes when using PICSI compared with conventional ICSI; however, the majority of studies are underpowered. Recently, a large, multicenter, randomized controlled trial, known as the Hyaluronic Acid Binding Sperm Selection (HABSelect) trial, found a significant reduction in miscarriage rates with PICSI, but no significant effect on live birth rate. There are still many avenues through which PICSI may provide an advantage, subject to confirmation by future research, such as improved long-term health of offspring. Other advanced sperm selection techniques include intracytoplasmic morphologically selected sperm injection, magnetic-activated cell sorting, and Zeta potential sperm selection; however, the most recent Cochrane review concluded that there is currently insufficient evidence to ascertain whether these techniques improve clinical outcomes, such as live birth rates.
Keywords: sperm selection; hyaluronic acid; PICSI; IMSI; MACS; Zeta potential